G‐C3N4‐Supported Metal‐Pair Catalysts toward Efficient Electrocatalytic Nitrogen Reduction: A Computational Evaluation. Issue 6 (26th February 2022) - Zhang, Zeyun; Xu, Xuefei
Abstract: Ambient electrocatalytic nitrogen reduction reaction (eNRR) is a low‐cost and clean method for large‐scale ammonia production. In this work, the authors investigate systematically the potential of 17 3d–5d double‐atom metal‐pairs catalysts supported on graphitic carbon nitride monolayer (M2 @g‐C3 N4 ) toward efficient eNRR. Two thermodynamically stable catalysts, V2 @g‐C3 N4 and Ni2 @g‐C3 N4, are identified as excellent candidates with low limiting potentials, small ammonia desorption free energies, and a high catalytic selectivity over the competing hydrogen evolution reaction (HER). The good performances toward eNRR of the two catalysts are both attributed to the cooperation effect of double active sites on nitrogen adsorption and on the early hydrogenation steps; it breaks the intrinsic linear scaling relationships between the adsorption energies of N‐containing intermediates and balances the competing needs of a good eNRR catalysts under the help of additional N2 adsorption: a low limiting potential, a small ammonia desorption energy, and a superior ability to suppress the HER. The other considered M2 @g‐C3 N4 behave more like a tuned single‐atom catalyst in the eNRR process, and thereby do not exhibit the expected eNRR activity. Abstract : By screening of metal‐pair catalysts supported on g‐C3 N4 monolayer (M2 @g‐C3 N4 ), two thermodynamically stable catalysts, V2 @g‐C3 N4 and Ni2 @g‐C3 N4, are identified as excellent candidates for electrocatalytic nitrogen reduction reaction (eNRR). The outstanding eNRR performance of two catalysts has been ascribed to the effective cooperation of the double metal active sites and the help of additional N2 adsorption.